Accommodation, empowerment and disinvestment—Typical second-language learning trajectories of Syrian refugees in Germany - Stefan Bernhard (International Migration, 2022)
This paper asks how refugees' second-language learning processes are embedded in their lives in host countries. To address this question, the paper proposes the concept of second-language learning trajectories. These trajectories explain refugees' second-language learning as closely intertwined with learners' self-understanding, experiences and positioning in host countries. Using longitudinal narrative interview data from Syrian refugees in Germany, the paper identifies three different types of second-language learning trajectories, that is empowerment, accommodation and disinvestment. These trajectories have vastly diverse outcomes, not only in terms of second-language proficiency but also in terms of learning motivation, self-views and future prospects. Moreover, second-language learning trajectories evolve based on self-reinforcing dynamics that make switching between trajectories increasingly difficult over time. This is particularly detrimental to refugees on the disinvestment trajectory, which entails social decline and exclusion. The paper also identifies institutional regulations in Germany that compound refugees' struggles to gain a foothold in their host country.
Keywords: 300